2006
DOI: 10.1002/ijc.21327
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for HPV infection and cervical cancer among unscreened women in a high-risk rural area of China

Abstract: We report a prevalence rate of 23.6% human papillomavirus (HPV) infection with oncogenic subtypes and 2.4% cervical intraepithelial neoplasia (CIN) III and cervical cancer (CC) in rural middle-aged women in 2 counties with the highest CC mortality in Shanxi Province, China. We examined the association of risk factors to HPV infection and to CIN III and CC in 8,798 unscreened women aged 35-50 years. Multivariate odds ratios (OR) and 95% confidence intervals (CI) for each endpoint were obtained for risk factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
24
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 41 publications
4
24
1
1
Order By: Relevance
“…Also, the prevalence of HPV infection in different age's group of women is 4% to 19.3% in different countries [12][13][14][15]. Other studies in Asia, reported the prevalence of HPV infections approximately 10%, 10.9%, 6.3% and 23.6% in South Korea, Southern Vietnam, Thailand and China respectively [8,9,16]. Given that similar work was performed in Tehran University of Medical Sciences and abnormal Pap specimens has been reported in 5 to 6 percent [17].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Also, the prevalence of HPV infection in different age's group of women is 4% to 19.3% in different countries [12][13][14][15]. Other studies in Asia, reported the prevalence of HPV infections approximately 10%, 10.9%, 6.3% and 23.6% in South Korea, Southern Vietnam, Thailand and China respectively [8,9,16]. Given that similar work was performed in Tehran University of Medical Sciences and abnormal Pap specimens has been reported in 5 to 6 percent [17].…”
Section: Discussionmentioning
confidence: 96%
“…Shin HR and colleagues have reported that the prevalence of HPV infection in sexually active women 20-74 y old in South Korea was 10.4% [8]. On the other hand, Zhao et al, in China, found oncogenic subtypes in 23.6% of middle-aged women [9]. Epidemiological data shows that High-risk oncogenic genital HPV-16 and 18 are the most frequently detected types in CCs worldwide [10].…”
Section: Introductionmentioning
confidence: 99%
“…Few population-based studies exist describing the epidemiology of HPV and cervical cancer among Chinese women younger than 25 years old as well as their knowledge of HPV and attitudes towards HPV vaccination [7][8][9][10][11][12][13] . Our study bridged this gap, demonstrating the high cervical cancer disease burden of sampled Chinese women aged 18-25.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have demonstrated that the prevalence of CIN and HPV infection varies by age [4][5][6] . Though several population-based screening studies reported the prevalence of HPV infection and CIN in China [7][8][9][10][11][12][13] , most studies focused on women older than 30 or 35. Very few data exist describing HPV and CIN prevalence among Chinese women younger than 25 years old.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, while cervical cancer mortality appears to have declined considerably in urban China between 1987 and 1999, this is less marked in rural areas (Yang et al, 2003b). A recent study in one such high-risk rural area, Shanxi Province, revealed that 23.6% of women aged 35 -50 years were infected with high-risk HPV types (Zhao et al, 2006). However, at present no population-based data are available on HPV prevalence across a broader age range of Chinese women, nor on the relative frequency of individual HPV types.…”
mentioning
confidence: 99%